DESKRIPSI KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH URBAN PADA MATERI FISIKA - Amnuel, Pesakh Rafaelovich; Sinaga, Feliza Paramitha; Winda, Febriana Rosa (EduFisika: Jurnal Pendidikan Fisika, 2023)
Critical thinking skills must be applied to students to evaluate information in the future. This study aims to describe students' critical thinking abilities in several Jambi and Lankaran schools in temperature and heat. The research method is mixed with a sample of 248 students in Jambi and Lankaran schools. The instruments used to collect quantitative data were essay questions that would be distributed to students. In contrast, qualitative data were obtained from interviews and supported by documentation studies relevant to the research topic. To analyze the data is done with SPSS-assisted descriptive statistics. The results obtained show students' critical thinking skills are high. The limitation of this research is that it only looks at students' critical thinking skills on temperature and heat. So that further research can add variables so that the results can be compared in more depth.